Prevalence of non-alcoholic fatty liver disease and its association with cardiovascular risk factors (data from Russian epidemiological studies) - O. M. Drapkina; S. E. Evstifeeva; S. A. Shalnova; V. A. Kutsenko; Yu. A. Balanova; A. E. Imaeva; A. V. Kapustina; M. B. Kotova; S. A. Maksimov; G. A. Muromtseva; O. A. Litinskaya; M. S. Pokrovskaya; et al. (Кардиоваскулярная терапия и профилактика, 2025)
Aim. To study the prevalence of non-alcoholic fatty liver disease (NAFLD) and its association with cardiovascular risk factors (RFs).Material and methods. The database from the ESSE-RF2 and ESSE-RF3 epidemiological studies was used, including data from surveys of population aged 35-64 years in 18 Russian regions (n=21204). To assess the prevalence of NAFLD, the fatty liver index (FLI) was used. Statistical analysis was performed using the statistical programming language and the R environment (version 3.6.1) with open-source code. The significance level for all tested hypotheses was p≤0,05.Results. Standardized prevalence rates of FLI ≥60 in the ESSE-RF3 study are slightly higher than in the ESSE-RF2 study (39,2% vs 42,3%, respectively). Multivariate analysis adjusted for sex, age, region, settlement type, and education showed significant associations of FLI ≥60 with hypertension, type 2 diabetes, hyperuricemia, lipid metabolism disorders, elevated high-sensitivity C-reactive protein levels, and cerebrovascular accident in men and women.Conclusion. Multivariate analysis confirmed the closest association of NAFLD with hypertension, type 2 diabetes mellitus, metabolic disorders, nonspecific inflammation, dyslipidemia, and cerebrovascular accident in men and women.